Effects of Fucoidan and Fucoidan Oligosaccharides in Growth and Quorum Sensing Mediated Virulence Factor of Campylobacter Jejuni - Sharon Palafox Félix; Giovanna Sandoval Larios; Rosina Cabrera; Alfonso García-Galaz; José Ángel Huerta-Ocampo; Ana María Guzmán-Partida; Rosa Idalia Armenta Corral; Jose Andrei Sarabia-Sainz; Gabriela Ramos Clamont Montfort (Polysaccharides)
Fucoidan is a sulfated fucan marine polysaccharide with potential therapeutic applications, including antibacterial activity and the control of virulence factors associated with quorum sensing. This study investigates the bioactivity of fucoidan derived from the brown algae Ascophyllum nodosum, as well as their fucoidan oligosaccharides (OFuc; <3 kDa), on the growth, motility, biofilm formation, and adhesion of Campylobacter jejuni, the leading cause of bacterial gastroenteritis worldwide. The results showed that fucoidan decreased the growth rate of C. jejuni at concentrations greater than 25 µg/mL, while no effect was observed with different concentrations (5–100 µg/mL) of OFuc. Neither compound affected bacterial motility. Both fucoidan and OFuc inhibited abiotic biofilm formation and diminished pathogen adhesion in a concentration-dependent manner. The study also found that C. jejuni recognized the fucoidan molecule through an enzyme-like lectin assay (ELLA) showing a lectin-like adhesin-carbohydrate recognition. Overall, these results suggest the potential of fucoidan from A. nodosum for controlling abiotic biofilm formation in the food industry, and they open new avenues for research into the use of fucoidan as a molecule aimed at blocking infections caused by C. jejuni.